The Food Security Challenge for the Buffalo Meat Industry: Perspectives from Lao PDR - Nampanya, Sonevilay; Young, James; Bush, Russell; Windsor, Peter; Khounsy, Syseng (Journal of Buffalo Science, 2014)
The Asiatic swamp buffalo (Bubalus bubalis) is an important livestock species in the Lao People’s Democratic Republic (Laos), with smallholder farmers owning the majority of an estimated 774,200 buffalo. Of the estimated 226,400 farm households with buffalo, 78% have a herd size of four or fewer, kept as a storage of wealth, sale for beef, for manure as fertilizer, and decreasingly, draught power. The total meat consumption in Laos and China was approximately 21 kg and 58 kg per capita in 2009, with an annual growth rate forecast of 4.5% and 3.1%. Increasing demand for meat in both domestic and neighboring markets offers opportunities for smallholders to gain more income from their livestock, particularly buffalo. However improving buffalo production requires numerous management constraints to be addressed, including: health issues (parasites and endemic diseases, particularly Toxocara vitulorum and Haemorrhagic Septicaemia control), biosecurity and transboundary disease (Foot and Mouth Disease control), nutritional deficits, low reproductive performance, high slaughter rates of pregnant cows, undeveloped trade and marketing systems, limited veterinary and extension service capacity, and potentially climate change and policy impacts. This paper reviews available information on these constraints to identify remaining gaps in knowledge and offer potentially suitable strategic interventions aimed at increasing the supply of buffalo in Laos. With the current rapid rate of economic development expected to continue in Laos and the Greater Mekong Subregion, expansion of the domestic and regional markets for food requires a more biosecure and sustainable supply of safe meat. Improving livestock health, productivity, processing and marketing, particularly of buffalo, is critical to ensuring poor smallholder communities can participate in and access these growing markets, providing improved rural livelihoods, poverty reduction and increased food security.